2021
DOI: 10.3389/fped.2021.710785
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Past SARS-CoV-2 Infections: A Prospective Cohort Study Among Swiss Schoolchildren

Abstract: Objective: To assess the predictive value of symptoms, sociodemographic characteristics, and SARS-CoV-2 exposure in household, school, and community setting for SARS-CoV-2 seropositivity in Swiss schoolchildren at two time points in 2020.Design: Serological testing of children in primary and secondary schools (aged 6–13 and 12–16 years, respectively) took place in June–July (T1) and October–November (T2) 2020, as part of the longitudinal, school-based study Ciao Corona in the canton of Zurich, Switzerland. Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
3
5
0
Order By: Relevance
“…In our study, six of a total of twelve confirmed seropositive children (50.0%) at baseline did not know that they had undergone SARS-CoV-2 infection. The finding of an underdiagnosis of SARS-CoV-2 infection in children is in accordance with two other investigations [ 10 , 11 ] although the extent of underdiagnosis varied between studies [ 12 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, six of a total of twelve confirmed seropositive children (50.0%) at baseline did not know that they had undergone SARS-CoV-2 infection. The finding of an underdiagnosis of SARS-CoV-2 infection in children is in accordance with two other investigations [ 10 , 11 ] although the extent of underdiagnosis varied between studies [ 12 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…Diverse test strategies have been implemented in schools to detect SARS-CoV-2 since the first school closures in Spring, 2020. Participation rates were notably higher when gargle 37 or saliva 38 samples were employed than when oral 30 or nasopharyngeal 39 swabs were taken. Gargle samples were provided for pool testing by 63% of pupils in a study in Austria, before renewed school closures 37 and by 83% of pupils in STACADO.…”
Section: Discussionmentioning
confidence: 91%
“…The high participation rate, at 73%, may be explained by the non-invasiveness of the sample collection. By contrast, mouth/throat swabs, taken by study personnel for PCR-analysis, were offered in Zurich, with an uptake rate of 49% 30 . The high participation rate in providing saliva samples could also be because the target population had had contact with a positive case, however 38 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations